Adaptation of Nusantara Fable Story in a Circus Show - Mulyosantoso, Greta Ariati; Wempi, Chrisdina (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020)DO - 10.24191/idealogy.v5i2.225, 2020)
Along with the times, traditional arts slowly began to fade. So, it is with traditional folk tales. It is important to keep traditional stories known and understood by children. Introducing the arts, especially performing arts, can be done from an early age, carried out by parents, teachers, to certain communities. For children, of course, an easy and interesting way is needed so that they can be enjoyed until a show is over. The concept of the show 'The Fabulous Fable Show; Circus and Theater 'is a concept that was initiated as a form of love for the local culture of the archipelago, collaborated with circus performances as one of the main branches of the performing arts. Circus shows generally feature attractions such as juggling, spinning, acrobatics, or attractions that use animals such as lions, tigers, elephants, and others. To make this show even more interesting, the concept maker included a theatrical element by bringing up the fable story from Indonesia. The fable story was chosen because the characters used were taken from animals and made children interested in the play that was performed. From there, children can recognize emotional expressions, such as joy or sadness that arise from a dance movement or song that is played. Keywords: Circus, Fable, Indonesia, Performing Arts